2012
DOI: 10.1128/jvi.05785-11
|View full text |Cite
|
Sign up to set email alerts
|

The Virion-Associated Open Reading Frame 49 of Murine Gammaherpesvirus 68 Promotes Viral Replication both In Vitro and In Vivo as a Derepressor of RTA

Abstract: Replication and transcription activator (RTA), an immediate-early gene, is a key molecular switch to evoke lytic replication of gammaherpesviruses. Open reading frame 49 (ORF49) is conserved among gammaherpesviruses and shown to cooperate with RTA in regulating virus lytic replication. Here we show a molecular mechanism and in vivo functions of murine gammaherpesvirus 68 (MHV-68 or ␥HV-68) ORF49. MHV-68 ORF49 was transcribed and translated as a late gene. The ORF49 protein was associated with a virion, interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…PF-8 was sufficient to induce PARP-1 downregulation. In addition to RTA and ORF49, ORF59 was shown to interact with PARP-1 in a genome-wide yeast two-hybrid screen of MHV-68 (8,11,24), although this interaction has not been validated in mammalian cells. KSHV ORF59 encodes PF-8, which is essential for virus genome replication (13)(14)(15)25) as an early late protein (26,27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PF-8 was sufficient to induce PARP-1 downregulation. In addition to RTA and ORF49, ORF59 was shown to interact with PARP-1 in a genome-wide yeast two-hybrid screen of MHV-68 (8,11,24), although this interaction has not been validated in mammalian cells. KSHV ORF59 encodes PF-8, which is essential for virus genome replication (13)(14)(15)25) as an early late protein (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…PARP-1 is also known to be a component of the viral replication complex, increasing viral genome replication (9,12). Previously, we showed that open reading frame 49 (ORF49) of MHV-68 interacts with PARP-1, disrupting interactions between RTA and PARP-1 and further promoting lytic replication by enhancing RTA-mediated transactivation (11). Here we report another viral strategy that modulates the activity of PARP-1 to facilitate the lytic replication of gammaherpesvirus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In KSHV, this is governed by the transcriptional control facilitated by RTA, and studies have demonstrated that ORF49 KSHV and its homologs are able to cooperate with RTA to enhance its transcriptional activation (13,(16)(17)(18)(20)(21)(22). However, the underlying mechanism of this process is still unclear, with limited functional studies and lack of structural information.…”
Section: Discussionmentioning
confidence: 99%
“…Another KSHV-encoded protein, the open reading frame 49 protein (ORF49 KSHV ), has been shown to upregulate the transcriptional activity of RTA (18). The protein homologs of ORF49 KSHV in Epstein-Barr virus (EBV) and murine herpesvirus 68 (MHV-68) display similar effects in the respective viruses (19)(20)(21)(22). ORF49 KSHV has been demonstrated to enhance lytic replication in KSHV, while the lack of the ORF49 MHV-68 protein has been shown to attenuate viral growth of MHV-68 (23).…”
mentioning
confidence: 87%